Mejoramiento de la cadena de suministro agroalimentaria para mitigar la mala nutrición y el hambre en el municipio de Boyacá – Boyacá (2023)
Through the following research we seek to improve the supply chain of the municipality of Boyacá as it finds shortcomings in the objectives with the UN and the proposed sustainable development goals for 2030; in addition to what there are indices of poor nutrition in the municipality since they consume the food they harvest therefore a research based on Analyse the supply chain and the agri-food system through tools such as survey and interview applied with the Scor model posing to evaluate its status and be able to identify strategies, was identified through the collection of data based on the Scor model how they manage the supply chain and nutrition of the inhabitants of the municipality of Boyacá- Boyacá Taking the data to a Likert scale.